Quantification of Temperature‐Dependent Charge Separation and Recombination Dynamics in Non‐Fullerene Organic Photovoltaics. (28th August 2021) - Chan, Christopher C. S.; Ma, Chao; Zou, Xinhui; Xing, Zengshan; Zhang, Guichuan; Yip, Hin‐Lap; Taylor, Robert A.; He, Yan; Wong, Kam Sing; Chow, Philip C. Y.
Abstract: Transient optical spectroscopy is used to quantify the temperature‐dependence of charge separation and recombination dynamics in P3TEA:SF‐PDI2 and PM6:Y6, two non‐fullerene organic photovoltaic (OPV) systems with a negligible driving force and high photocurrent quantum yields. By tracking the intensity of the transient electroabsorption response that arises upon interfacial charge separation in P3TEA:SF‐PDI2, a free charge generation rate constant of ≈2.4 × 10 10  s −1 is observed at room temperature, with an average energy of ≈230 meV stored between the interfacial charge pairs. Thermally activated charge separation is also observed in PM6:Y6, and a faster charge separation rate of ≈5.5 × 10 10  s −1 is estimated at room temperature, which is consistent with the higher device efficiency. When both blends are cooled down to cryogenic temperature, the reduced charge separation rate leads to increasing charge recombination either directly at the donor‐acceptor interface or via the emissive singlet exciton state. A kinetic model is used to rationalize the results, showing that although photogenerated charges have to overcome a significant Coulomb potential to generate free carriers, OPV blends can achieve high photocurrent generation yields given that the thermal dissociation rate of charges outcompetes the recombination rate. Abstract : In this study, transient optical spectroscopy methods are used to quantify the temperature dependence of charge generation dynamics in efficient non‐fullerene organic photovoltaic blends with a negligible driving force. The results show that the photogenerated electron–hole pairs can thermally separate at the D/A interface, given that they are sufficiently long‐lived (even at a reduced temperature for state‐of‐the‐art materials).